1987
DOI: 10.1152/ajpgi.1987.253.3.g351
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic taurine transport: a Na+-dependent carrier on the basolateral plasma membrane

Abstract: Highly purified rat basolateral liver plasma membrane vesicles were used to examine the mechanism and the driving forces for hepatic uptake of the beta-amino acid, taurine. An inwardly directed 100 mM NaCl gradient stimulated the initial rate of taurine uptake and energized a transient twofold accumulation of taurine above equilibrium ("overshoot"). In contrast, uptake was slower and no overshoot was detected in the presence of a KCl gradient. A negative intravesicular electrical potential generated by the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 0 publications
4
17
0
1
Order By: Relevance
“…2). Similar to results previously observed using membrane vesicles from adult rats (8), taurine uptake by membrane vesicles from developing rat liver decreased with increasing medium osmolarity and extrapolation of the derived linear regression curve to infinite osmolarity (theoretical intravesicular volume = 0) showed minimal binding of taurine.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…2). Similar to results previously observed using membrane vesicles from adult rats (8), taurine uptake by membrane vesicles from developing rat liver decreased with increasing medium osmolarity and extrapolation of the derived linear regression curve to infinite osmolarity (theoretical intravesicular volume = 0) showed minimal binding of taurine.…”
Section: Resultssupporting
confidence: 87%
“…adult rat liver (8). To determine whether nonspecific taurine binding to the membrane contributes to the observed age-related differences in taurine uptake, the effect of medium osmolarity on taurine uptake was assessed using membrane vesicles from developing rat liver (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies using rat hepatic plasma membrane vesicles showed Na + -dependent taurine uptake, of which the K m value (174-380 µM) was similar to the K m value of the mouse orthologue of GAT2 (540 µM, mouse GAT3), 5,59,60) and it is a conceivable that GATs on the sinusoidal membrane of periportal hepatocytes contribute to taurine uptake, followed by conjugation. In addition, the uptake study in isolated rat hepatocytes suggested Na + -and Cl − -dependent taurine uptake by hepatocytes, and the estimated a K m value (594 µM) was similar to that of mouse GAT3-mediated taurine transport.…”
Section: Hepatic Taurine Uptake Mediated By Gat2mentioning
confidence: 71%